Feasibility Analysis and Implementation of FreeCAD Open Source Computer-Aided Design (CAD) Software as an Alternative Replacement for Inventor Student Version Software - Isra, Muhammad; Zulfri, Muhammad; Fauzan, Fauzan; Harmin, Amalia; Rizqullah, Akbar; Rizki, Muhammad Nuzan (E-Journal Universitas Malikussaleh, 2025)
Industry 4.0 is supported by nine foundational pillars, including Big Data and Analytics, Autonomous Robots, Simulation, Horizontal and Vertical System Integration, the Industrial Internet of Things (IIoT), Augmented Reality, Cloud Computing, Additive Manufacturing, and Cybersecurity. This study focuses on horizontal and vertical system integration, which enables seamless information flow across departments, suppliers, and customers through smart systems and IoT devices. One important tool in supporting industrial integration is Computer Aided Design (CAD), which plays a key role in product design and the generation of blueprints that bridge design and manufacturing functions. Most widely used CAD software such as AutoCAD, SolidWorks, Inventor, and CATIA are commercial and come with high licensing costs. At Samudra University, Autodesk Inventor Student Version was previously utilized for educational purposes; however, due to its feature limitations and temporary license, an alternative was sought. In collaboration with the Mechanical Engineering Department, FreeCAD was explored as an Open Source solution. This research aims to identify a free and open-source CAD software that offers features comparable to commercial CAD tools and can be further developed without licensing constraints. The methodology involves collecting various Open Source CAD applications, establishing evaluation criteria, testing core functionalities, and selecting the most suitable application to support academic and industrial design needs.